Modeling of the Foca-Uzunada magnetic anomaly and thermal structure in the gulf of Izmir, western Turkey. (1st May 2018) - Aydemir, Attila; Bilim, Funda; Cifci, Gunay; Okay, Seda
Graphical abstract: Highlights: Magnetic anomaly in the Gulf of Izmir, Turkey was modeled in this study. The top of the causative body is shallow at about 0.5 km in the outer gulf. Top depth is consistent with the basement in seismic lines crossing the anomaly. Geometry of the basement in seismic sections are also consistent with the 3D model. The slope of the causative body is through the E-NE in the thermal and model maps. Curie Point Depth values vary from 7 km in the NE of Foca to 10 km to the south. Abstract: The Gulf of Izmir (GoI) is one of the largest gulfs in the Aegean Sea, Turkey. There is a large magnetic anomaly extending in the NE-SW direction between Foca and Uzunada (Uzun Island) in the gulf. Previously, Curie Point Depth (CPD), geothermal gradient, heat-flow and radiogenic heat production maps of the onshore part of the Aegean region were constructed from the aeromagnetic data. In this study, the same maps except radiogenic heat production map are presented for the offshore part and the largest magnetic anomaly in the northern part of the gulf is focused, particularly. As a result, the thermal structure of GoI is clearly defined and according to the results of this study, CPD values were found from 7 km in the NE of Foca to 10 km through the south of the gulf. The geothermal gradient values vary between 50 and 80 °C/km. Maximum heat flow values around the anomaly are calculated as 200 and 215 mW/m 2 according to the thermal conductivity coefficients of 2.5 W m −1 K −1 and 2.7 W m −1 K −1, respectively. Although the anomaly is located in the Izmir Gulf; CPD, geothermic gradient, heat flow anomalies are shifted through the north of Foca and Aliaga towns in the Candarli Bay. This prominent anomaly in the Gulf of Izmir is associated with the magmatics that were encountered at 969 m in the Foca-1 well although it was drilled about 2 km away from the outermost closed contour of the magnetic anomaly. The anomaly is also modeled three dimensionally (3D) in this study. In the model map, the top of the causative body is completely located in the outer part of the gulf, and is very shallow at about 0.5 km while its bottom is inclined through the west of Cigli and Menemen. From this viewpoint, it is possible to suggest that the causative body is inclined through the Foca Peninsula. However, its closed contours are in the NE direction, through the Candarli Bay. Top depth of the causative body is also calculated from the basement horizon on the seismic sections crossing this anomaly. Depth calculations are consistent in these sections and confirm the top depths from the modeling study. The basement geometry in the seismic sections also reflects the shape of 3D model geometry, and bottom depth of the magmatics is also verified by the basement depth calculations in seismic sections.